Exploring learners’ perceptions of Project-Based Learning (PBL) in improving productive language skills - Baharudin, Muhammad Danial; Mohd Radzi, Khadijah; Wan Yusof, Wan Putri Zaharah (Perpustakaan Negara Malaysia, 2023)
Research has indicated that the majority of learners experienced difficulty in improving writing and speaking skills when doing project-based learning activities in classes. This qualitative research aims to explore learners’ perceptions of the role of project-based learning in improving their writing and speaking skills. Three participants were chosen for this study using purposive sampling. The findings indicated that with the PBL activity “Recycle Rally”, learners have shown improvement in their productive language skills such as Writing and Speaking. Based on the qualitative analysis, the learners perceived that PBL has helped them improve their grammar and vocabulary as well as organise the ideas in writing by using an outline. Besides that, they also felt that they could enhance their speaking abilities by actively engaging in English interactions and communications through PBL which resulted in them becoming more confident in using English. Overall, PBL does improve the learners’ productive language skills.